University social responsibility under the influence of societal changes: Students’ satisfaction and quality of services in Saudi Arabia - Alghamdi, Abdulelah A. (Frontiers in Psychology, 2022)
Universities contribute to shaping the identity of a nation with their major university social responsibility (USR) in addition to their academic purposes and corporate strategies. In Saudi Arabia with Vision 2030, universities are facing a transformation in adapting to the societal changes and implementing a socially responsible management, considering the satisfaction of their most important stakeholders (i.e., the students) and the quality of services offered to them. This study aims to explore how USR fulfils the societal changes in Saudi Arabia from the perspective of university students in addition to inspecting USR’s relationships with the students’ satisfaction and the quality of services offered to them. A self-report study was conducted with 350 undergraduate students in the Faculty of Social Sciences in a Social Work program at a University in the Western region of Saudi Arabia. An inside–outside (I–O) map of USR was applied to investigate the relationships among USR’s aspects. The study results demonstrated a moderate level of agreement by students toward the university’s fulfilment of its USR, quality of services offered to them, and their satisfaction. In contrast, the results of a regression analysis revealed that all USR aspects could explain only 13% of the students’ satisfaction. Legal responsibilities, among all USR aspects, exhibited the highest influence on students’ satisfaction. Gender differences existed in favor of female students’ perceptions toward the university’s fulfilment of its USR. The I–O map provided interesting insights to interpret the correlations among all USR aspects under the influence of societal changes that have occurred under Saudi Vision 2030